Motor deficits and beta oscillations are dissociable in an alpha‐synuclein model of Parkinson's disease. (22nd April 2017) - Brys, Ivani; Nunes, Jessica; Fuentes, Romulo
Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterised by progressive motor symptoms resulting from chronic loss of dopaminergic neurons in the nigrostriatal pathway. The over expression of the protein alpha‐synuclein in the substantia nigra has been used to induce progressive dopaminergic neuronal loss and to reproduce key histopathological and temporal features of PD in animal models. However, the neurophysiological aspects of the alpha‐synuclein PD model have been poorly characterised. Hereby, we performed chronic in vivo electrophysiological recordings in the corticostriatal circuit of rats injected with viral vector to over express alpha‐synuclein in the right substantia nigra. Our model, previously shown to exhibit mild motor deficits, presented moderate dopaminergic cell loss but did not present prominent local field potential oscillations in the beta frequency range (11–30 Hz), considered a hallmark of PD, during the 9 weeks after onset of alpha‐synuclein over expression. Spinal cord stimulation, a potential PD symptomatic therapy, was applied regularly from sixth to ninth week after alpha‐synuclein over expression onset and had an inhibitory effect on the firing rate of corticostriatal neurons in both control and alpha‐synuclein hemispheres. Dopamine synthesis inhibition at the end of the experiment resulted in severe parkinsonian symptoms such as akinesia and increased beta and high‐frequency (>90 Hz) oscillations. These results suggest that the alpha‐synuclein PD model with moderate level of dopaminergic depletion does not reproduce the prominent corticostriatal beta oscillatory activity associated to parkinsonian conditions. Abstract : Prominent field potential beta oscillatory neural activity associated to Parkinson's disease is suggested to play a mechanistic role in motor deficit. We show that an alpha‐synuclein model with moderate dopaminergic cell loss and motor deficit does not display such oscillations, unless challenged with further dopamine depletion. These results indicate that beta oscillations and motor deficits can be dissociated and raises questions about the role of beta oscillations in parkinsonian conditions.